SAT0263 Comparison between TOCILIZUMAB and Alternatve TNF Inhibitor as A Second Line following TNF Inhibitor Failure in Patients with Rheumatoid Arthritis. (10th June 2014) - Kunishita, Y.; Yoshimi, R.; Kishimoto, D.; Kamiyama, R.; Minegishi, K.; Hama, M.; Kirino, Y.; Asami, Y.; Yamazaki, T.; Sekiguchi, A.; Suda, A.; Ideguchi, H.; et al.
Abstract : Background: Both TNF inhibitor (TNFi) and non-TNFi biologics can be the first biologics for patients with rheumatoid arthritis (RA) in 2013 EULAR recommendations, whereas definitive therapeutic algorithm is not shown in RA patients who failed to respond to a particular biologics as the first line. In non-responders to the first TNFi, superiority of non-TNFi biologics to alternative TNFi as the second choice is suggested by the high drug retention rate. Objectives: To compare clinical responses of tocilizumab with that of TNFi as the second biologics in RA patients after treatment failure with a TNFi as the first choice. Methods: Patients with RA who were registered in Y-CURD, the integrated database of patients at our department and its affiliated hospitals, and have been treated with TNFi (infliximab, etanercept, adalimumab) as the first biologics followed by another biologics. They were divided into two groups, TT group (TNFi – TNFi) and T6 gourp (TNFi – tocilizumab). We compared the clinical efficacy of the second biologics by assessing DAS28-ESR and the individual components between the two groups for 12 months after switching biologics. Results: Among 86 patients recruited, 57 and 29 belonged to TT and T6 groups, respectively. There was no significant difference in the reasons for switching biologics ( p =0.41): in TT group, primary non-response in 18, secondary non-response in 37, and other reasons in 2, while in T6 group, primary non-response in 6, secondary non-response in 22, and adverse effect in 1. There was no significant difference in other baseline parameters, including TJC, SJC, PGA, and DAS28-ESR, between the two groups. DAS28-ESR was significantly reduced during the first 3 months after switching in both groups, though the reduction was larger in T6 group than TT group (2.72±1.14 vs 1.43±1.55, p =0.0005). Further sustained reduction of DAS28-ESR was found in T6 group, but not TT, from 3 to 12 months after switching. Of the individual components of DAS28, tender joint count and patient global assessment were significant decreased in T6 group compared to TT group at 12 months (0.38±0.62 vs 2.54±4.11, p =0.027, and 14.3±17.3 vs 28.1±24.0, p =0.031, respectively). Conclusions: Our data showed that tocilizumab was more effective as the second biologic than alternative TNFi in RA patients who had previously treated with a TNFi as the first biologics. As tocilizumab might be an appropriate biologic as the first choice in such cases, further analyses as to the clinical characteristics of more accumulated cases can provide clues to optimized selection of biologics. References: Du Pan SM et al. Differential drug retention between anti-TNF agents and alternative biological agents after inadequate response to an anti-TNF agent in rheumatoid arthritis patients. Ann Rheum Dis 2012;71:997-9. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5168